2013
DOI: 10.5581/1516-8484.20130115
|View full text |Cite
|
Sign up to set email alerts
|

Gene rearrangement study for minimal residual disease monitoring in children with acute lymphocytic leukemia

Abstract: ObjectiveTo detect markers for minimal residual disease monitoring based on conventional polymerase chain reaction for immunoglobulin, T-cell receptor rearrangements and the Sil-Tal1 deletion in patients with acute lymphocytic leukemia. MethodsFifty-nine children with acute lymphocytic leukemia from three institutions in Minas Gerais, Brazil, were prospectively studied. Clonal rearrangements were detected by polymerase chain reaction followed by homo/heteroduplex clonality analysis in DNA samples from diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A low cost, reliable and easy to perform methodology is desired. This was precisely what Assumpção et al are presenting in their paper published in this issue of Revista Brasileira de Hematologia e hemoterapia ( 4 ) . These authors tried to detect markers in MRD monitoring based on conventional polymerase chain reaction (PCR) for immunoglobulin (Ig) and T-cell receptor (TCR) rearrangements, and Sil-Tal1 deletion in patients with acute lymphoblastic leukemia (ALL) treated in three hospitals in Minas Gerais, Brazil.…”
mentioning
confidence: 54%
“…A low cost, reliable and easy to perform methodology is desired. This was precisely what Assumpção et al are presenting in their paper published in this issue of Revista Brasileira de Hematologia e hemoterapia ( 4 ) . These authors tried to detect markers in MRD monitoring based on conventional polymerase chain reaction (PCR) for immunoglobulin (Ig) and T-cell receptor (TCR) rearrangements, and Sil-Tal1 deletion in patients with acute lymphoblastic leukemia (ALL) treated in three hospitals in Minas Gerais, Brazil.…”
mentioning
confidence: 54%
“…Alternatively, some authors have proposed the detection of Ig/TCR rearrangements by conventional PCR using consensus primers and homo/heteroduplex analysis, despite its lower analytical sensitivity, considering that this approach allows identification of patients with greater residual tumor burden, and then at high risk of relapse. 22 , 27 , 49 , 50 , 78 , 79 , 87 , 88 …”
Section: Discussionmentioning
confidence: 99%
“…Another study in acute lymphoblastic leukemia patients measuring Ig/TCR by Real-time PCR found that risk stratification of precursor B-ALL, not T-ALL, could be improved by using MRD measurement on day 15 and day 33 instead of day 33 and day 79 in similar BFM protocols for patients with these diseases. According to Assumpção et al (2013), measuring Ig/TCR by PCR followed by homo/heteroduplex clonality analysis, found MRD independent prognostic factor for leukemia-free survival and overall survival even when based on a non-quantitative technique but longer follow-up always needed. Foroni et al (2005) reported that flow cytometry in childhood T-ALL is a favorable prognostic marker in peripheral blood and bone marrow samples.…”
Section: Genetic Monitoring Of Mrd In Acute Lymphoblastic Leukemiamentioning
confidence: 99%